Measuring the change in functional level of children rehabilitants with cerebral palsy: a brief report - Zholtay Daribayev; Sholpan Bulekbayeva; Mikhail Saltychev; Yevgeny Lysovskyy; Natalya Lisovska; Kenzhe Kussainova (Finland, 2022)
To compare Gross Motor Function Measure (GMFM), Gross Motor Function Classification System (GMFCS), Functional Independence Measure (FIM®), Manual Ability Classification System (MACS), and Ashworth scale in their ability to discriminate larger and smaller benefits of rehabilitation. 248 children with cerebral palsy participated in an intensive rehabilitation intervention. Scores were assessed at admission and discharge. GMFCS and MACS scores did not change. Ashworth scale and FIM improved evenly in almost every rehabilitant. There were positive changes in GMFM scores of 233 rehabilitants with median pre/post difference 3.8 (range 0.4 to 29.2) points.  While Ashworth scale, FIM, GMFCS, and MACS might be valuable tools to assess the level of functioning, they seemed to be too rough to describe mild changes observable during a short rehabilitation intervention. Comparing to them, GMFM scale seemed to be more sensitive in defining such changes.